STRENGTH TRAINING AND HOMOCYSTEINE AND ITS RELATIONSHIP WITH CARDIOVASCULAR DISEASES (Fiep Bulletin - online, 2020)
Arterial hypertension (AH) has been pointed as the main risk factor for the development of cardiovascular diseases. The rates of individuals with hypertension have been increasing due to environmental factors, as well as pathophysiological factors such as increased serum homocysteine ??(Hci) levels. However, research involving strength training, its respective intensities and Hci levels is scarce and inconclusive. This systematic review aimed to identify in the literature studies that evaluated the effect of strength training on serum Hci levels and their contributions in the fight against cardiovascular disease. Exercise has been a source of study as a method for reducing circulating Hci levels. A search was performed in the PubMed, Lilacs, and Scielo databases using as descriptors the terms homocysteine ??associated with strength training. The selected articles were obtained in full and included in the sample. Regarding the intensity of strength training, two studies were performed with 75 to 80% of 1 RM, one research performed with 60% of 1 RM, one study used 50 to 80% of 1 RM and only one research was performed with 35% of 1 RM. 1 RM. This systematic review has shown that strength training can play an important role in reducing Hci plasma levels in middle-aged and elderly individuals undergoing a regular program of moderate to high intensity strength exercise, despite the mechanisms by which this reduction occurs. it is unclear.
Keywords: Cardiovascular diseases; Physical exercise; Homocysteine